A Complication of Mycobacterium chelonae Infection Following Orbital Floor Fracture Repair. Issue 4 (7th June 2021) - Ghodke, Ameer; Mims, Mark M.; Shah, Rupali N.; Clark, J. Madison
Abstract : Abstract: Mycobacterium chelonae is a rare, atypical nontuberculous bacterium that has been reported to be an underlying cause of persistent wound infections. Although there are several studies highlighting the role of M chelonae as the putative cause of other postoperative wound infections, to our knowledge there are no reports of infection following implant placement for repair of an orbital floor fracture. The authors present a unique case describing the management of a persistent postoperative infection in a young, immunocompetent patient with an orbital floor fracture repaired with a Stryker Medpor Titan implant. The patient was initially treated with broad-spectrum antibiotics with minimal clinical improvement. Following culture-proven M chelonae, a second surgical intervention was undertaken to remove the implant and later, a third intervention for scar revision. The patient has remained free of infection utilizing a long-term tailored 2-drug antibiotic regimen. This case emphasizes the need for recognition of M chelonae as a potential pathogen in certain clinical situations and the difficulty in eradicating M chelonae in the context of infected implantable devices. The comprehensive treatment protocol required to ensure adequate therapy is reviewed.